The Book of Real-World Negotiations - Weiss, Joshua (Ascent Audio, 2020)
This unique book can help you change your approach to negotiation by learning key strategies and techniques from actual cases. The Book of Real World Negotiations shines a light on real world negotiation examples and cases, rather than discussing hypothetical scenarios. It reveals what is possible through preparation, persistence, creativity, and taking a strategic approach to your negotiations. Many of us enter negotiations with skepticism and without understanding how to truly negotiate well. Because we lack knowledge and confidence, we may abandon the negotiating process prematurely or agree to deals that leave value on the table. The Book of Real World Negotiations will change that once and for all by immersing you in these real world scenarios. As a result, you'll be better able to grasp the true power of negotiation to deal with some of the most difficult problems you face or to put together the best deals possible. This book also shares critical insights and lessons for instructors and students of negotiation. Whether you're a student, instructor, or anyone who wants to negotiate successfully, you'll be able to carefully examine real world negotiation situations that will show you how to achieve your objectives in the most challenging of circumstances.